PEMBELAJARAN BAHASA INDONESIA TERINTEGRASI DENGAN ASPEK-ASPEK PRAGMATIK EDUKASIONAL UNTUK MAHASISWA JURUSAN NONBAHASA INDONESIA (Integrated Indonesian Language Learning with Educational Pragmatics Aspects for Non-Indonesian Language Students) - Pranowo Pranowo (Balai Bahasa Sulawesi Selatan, 2020)
The research is the result of conceptual research that examines the theories of the pragmatics of education, which integrated into the Indonesian language learning for non-Indonesian language students who have only used the linguistic approach. Pragmatics of education is language learning that integrates linguistic aspects to pragmatic aspects as an approach to learning the Indonesian language. The problem is, how is the integrating of linguistic and educational pragmatics aspects into Indonesian language learning for non-Indonesian language students? The research aims to describe the integrating of the feature of educational pragmatic in Indonesian language learning for non-Indonesian language students. Data sources include (a) Indonesian language learning material for non-Indonesian language students issued by the Research and Technology Department (2013), and (b) some journal articles and pragmatic books that are relevant to the topic of research. The research data has collected by reading and recording techniques from various sources. Data analysis techniques are done by (a) identifying data, (b) classifying data, and (c) critically examining the data findings. The results show that all pedagogical pragmatics aspects basically can be integrated into Indonesian language learning for non-Indonesian language students. However, due to Indonesian language learning for non-Indonesian language students is only focused on writing scientific essays, it is not necessary to have all aspects of the pragmatics of education to be included in the learning. Educational pragmatics aspects that need to be including are only (a) some of the communicative competencies, (b) some of the static and dynamic contexts in language, and (c) some of the politeness aspects in Indonesian language learning for non-Indonesian language students.AbstrakArtikel ini merupakan hasil penelitian konseptual yang mengkaji berbagai teori pragmatik edukasional untuk diintegrasikan dalam pembelajaran bahasa Indonesia bagi mahasiswa nonjurusan bahasa Indonesia yang selama ini hanya menggunakan pendekatan linguistik. Pragmatik edukasional adalah pembelajaran bahasa yang mengintegrasikan aspek-aspek linguistik dengan aspek-aspek pragmatik sebagai pendekatan pembelajaran bahasa Indonesia. Permasalahan kajian ini adalah “Bagaimanakah pengintegrasian aspekaspek linguistik dan aspek-aspek pragmatik edukasional ke dalam pembelajaran bahasa Indonesia bagi mahasiswa nonjurusan bahasa Indonesia?”. Tujuan kajian ini adalah mendeskripsikan pengintegrasian aspek-aspek pragmatik edukasional dalam pembelajaran bahasa Indonesia bagi mahasiswa nonjurusan bahasa Indonesia. Sumber data berupa (a) materi pembelajaran bahasa Indonesia bagi mahasiswa nonjurusan bahasa Indonesia yang diterbitkan oleh Ristek Dikti (2013) dan (b) berbagai artikel jurnal dan buku pragmatik yang relevan dengan topik kajian. Data kajian dikumpulkan dengan teknik baca dan catat dari berbagai sumber. Teknik analisis data dilakukan dengan (a) mengidentifikasi data, (b) mengklasifikasi data, dan (c) menelaah secara kritis hasil temuan data. Hasil kajiannya adalah semua aspek pragmatik edukasional pada dasarnya dapat diintegrasikan dalam pembelajaran bahasa Indonesia bagi mahasiswa nonjurusan bahasa Indonesia. Namun, pembelajaran bahasa Indonesia bagi mahasiswa nonjurusan bahasa Indonesia hanya difokuskan pada penulisan karangan ilmiah, tidak perlu semua aspek pragmatik edukasional dimasukkan dalam pembelajaran. Aspek pragmatik edukasional yang perlu dimasukkan hanya (a) beberapa kompetensi komunikatif, (b) beberapa konteks statis dan konteks dinamis dalam berbahasa, dan (c) beberapa aspek kesantunan dalam pembelajaran bahasa Indonesia bagi mahasiswa nonjurusan bahasa Indonesia.